ARP-HPLC STABILITY INDICATING METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS DETERMINATION OF NETUPITANT AND PALONOSETRON IN PHARMACEUTICAL DOSAGE FORM - CHANDAR, P. BHANU; MADHURI, M. SANDHYA; HYMA, K. NIRMALA; ANUSHA, S.; RASOOL, SK. NABI (International Journal of Current Pharmaceutical Research, 2022)
Objective: A simple, precise, sensitive, rapid, accurate, and specific method was developed and validated for the simultaneous determination of Netupitant and Palonosetron in Pharmaceutical dosage form. Methods: The separation was done on the ODS C18 column of dimensions (150 mm x 4.6, 5 μm) with the mobile phase 0.1N potassium dihydrogen orthophosphate pH 3.3 and acetonitrile in a 50:50 ratio, at a flow rate of 1.0 ml/min and injection volume of 10 μl. The optimum wavelength selected was 274 nm and the temperature of the column was maintained at 30 ℃. Results: The retention time was 2.199 min and 2.893 min and they were linear in the concentration range of 75-450 μg/ml and 0.125-0.75 μg/ml for Netupitant and Palonosetron, respectively. The repeatability and intermediate precision were found to be within acceptable limits. Regression equation of Netupitant and Palonosetron is Y=6329x+42914 and Y= 258884x+3103.9, respectively. LOD was found to be 0.33μg/ml, 0.99μg/ml and LOQ was 0.01μg/ml, 0.04μg/ml for Netupitant and Palonosetron. The correlation coefficient (R2) value was found to be 0.999 and %recovery was obtained as 100.32%and 99.6% for Netupitant and Palonosetron, respectively. Forced degradation studies reveal that the drugs are unstable under acidic conditions. Conclusion: The flexibility, accuracy, precision of the developed method ensures applicability in routine analysis of pharmaceutical dosage form.